2016
DOI: 10.4236/health.2016.814146
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Preventive Practices on Ebola Virus Disease in the Kintampo Districts of Ghana

Abstract: This study describes community members' knowledge of Ebola Virus Disease (EVD), their attitudes and preventive practices. A mixed methods approach was used. A random sample of 1028 community members aged 15 -65 years was interviewed in a quantitative survey. This was complemented with a qualitative study involving 24 opinion leaders who were carefully selected. The study was conducted in Kintampo North and South districts of Ghana from August 2014 to October 2014. 83% of respondents had heard of EVD, but 62.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…From our study, most of those who knew VHF named mass media, specifically radio, as their main sources of information. Similar findings have been reported in previous studies in Tanzania and elsewhere in Africa [ 30 , 31 ].This indicates that mass media channels, are important sources of information. Three-quarters of the study participants had unfavourable attitudes toward VHF.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…From our study, most of those who knew VHF named mass media, specifically radio, as their main sources of information. Similar findings have been reported in previous studies in Tanzania and elsewhere in Africa [ 30 , 31 ].This indicates that mass media channels, are important sources of information. Three-quarters of the study participants had unfavourable attitudes toward VHF.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is concurrent with a study conducted in Guinea where educated people had better knowledge on EVD than those not educated [ 18 ]. In a study in Ghana, people with no education, those not working were reported to be the least knowledgeable in EVD [ 31 ]. Educational level, monthly income has been reported to be significantly associated with practices as regards to infectious disease prevention and control [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Strategies to halt the spread of the Ebola virus included strict policy on hand washing with soap and alcohol, sanitary funeral practices, case isolation and contact-tracing with quarantine (Pandey et al, 2014). Nettey et al (2016) concur with these findings where they reported strict implementation to improve hand hygiene among others measures, thereby combating the spread of Ebola virus disease.…”
Section: Predictors Of Handwashingmentioning
confidence: 55%
“…As a result, ignorance at the epidemic alert threshold and the attitude to take in the suspect person may have consequences for the increase of suspected and contorted cases [2] [12] [14].…”
Section: Introductionmentioning
confidence: 99%